The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/biom11101496
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Cerebrospinal Fluid Matrix Metalloproteinases Levels and Brain Amyloid Deposition in Mild Cognitive Impairment

Abstract: This study aimed to explore whether cerebrospinal fluid (CSF) levels of matrix metalloproteinases (MMPs), and their inhibitors (TIMPs) were associated with brain amyloid deposition, cortical glucose metabolism, and white matter lesions (WMLs) in individuals with amnestic mild cognitive impairment (MCI). A total of 33 individuals with amnestic MCI (mean age, 75.6 years) underwent 11C-Pittsburgh compound B positron emission tomography (PiB-PET), 18F-fluorodeoxyglucose positron emission tomography, magnetic reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…In related work, amyloid deposition is reduced in mice engineered to express high levels of MMP-9 ( Fragkouli et al, 2014 ; Yang et al, 2015 ). Similarly in human CSF, MMP-2 which shares substrate similarity with MMP-9, is negatively correlated with amyloid deposition as assessed by Pittsburgh compound B labeling ( Sasaki et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In related work, amyloid deposition is reduced in mice engineered to express high levels of MMP-9 ( Fragkouli et al, 2014 ; Yang et al, 2015 ). Similarly in human CSF, MMP-2 which shares substrate similarity with MMP-9, is negatively correlated with amyloid deposition as assessed by Pittsburgh compound B labeling ( Sasaki et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in amyloid depositing mice engineered to express high levels of MMP-9, amyloid deposition is also reduced (Fragkouli et al ., 2014; Yang et al ., 2015). Similarly in human CSF, MMP-2 which shares substrate similarity with MMP-9, is negatively correlated with amyloid deposition as assessed by Pittsburgh compound B labeling (Sasaki et al ., 2021). In a related study MMP-9 levels are reduced in AD patients as compared to controls (Mroczko et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, the co-occurrence of AD in these patients can significantly confound results when extrapolating these results to CAA pathology. Additionally, CSF MMP-2 has been shown to be associated with parenchymal amyloid deposition [ 37 ]. MMP activity studies using gelatin zymography have shown MMP-9 activity to be elevated in CSF of patients with vascular dementia, but not in patients with AD, when compared to controls [ 38 ].…”
Section: Introductionmentioning
confidence: 99%